MASSAGE PUNGGUNG EFEKTIF MENURUNKAN SKALA NYERI IBU POST SECTIO CAESAREA - Eka Widi Rimadini; Endah Kusuma Wardani; Ervia Toga (Ensiklopedia Research and Community Service Review, 2026)
A Caesarean Section (CS) is a surgical procedure performed by an obstetrician on the mother's abdomen in the uterus. One of the effects of surgery is pain in the stitches. One method to reduce pain is with complementary therapy, back massage. This study aims to analyze the effectiveness of back massage on changes in pain scales in post-CS mothers at Genteng Regional General Hospital, Banyuwangi. This study is a quasi-experimental study with a pre-test and post-test design approach with a control group. The subjects of this study were 30 post-CS mothers in the delivery room of Genteng Regional General Hospital, selected by Consecutive Sampling and divided into 2 groups, each consisting of 15 people. The intervention in the form of back massage was given for 3 days with a duration of 20 minutes of back massage. Data were analyzed using the Mann-Whitney test. The results of this study showed that in the control group, the average pain scale was 5.267 and after receiving post-CS care it became 2.267. In the treatment group, the average pain scale was 5.000 and after receiving intervention it became 1.200. Back massage effectively reduced the pain scale of post-cesarean mothers (ρ = 0.030 0.05). These results suggest that midwives can apply back massage therapy as a non-pharmacological complementary therapy for post-cesarean mothers to contribute to reducing pain intensity.Keywords: back massage, post sectio caesarean, level of pain, complementary therapy